2019
DOI: 10.5847/wjem.j.1920-8642.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with Haff disease after eating crayfish

Abstract: BACKGROUND: The study aimed to explore the clinical presentations, laboratory findings, treatments and prognosis of patients with Haff disease after eating crayfi sh. METHODS: Sixteen patients with Haff disease after eating crayfish were admitted to the Emergency Department of Beijing Chao-yang Hospital between June 2013 and August 2017. Clinical data was retrospectively analyzed. RESULTS: Alcohol consumption and exercise were found to be most commonly associated with the onset of rhabdomyolysis after consumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…ALT, AST, Mb, and LDH were also abnormally elevated in more than 80% of patients [23]. In severe cases, acute renal failure occurs, leading to elevated BUN indexes [23]. In this study, it was found that the indexes of CK, ALT, AST, LDH, and BUN in mice treated with 3.5 mg•kg −1 and 7 mg•kg −1 of maduramicin were significantly increased in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…ALT, AST, Mb, and LDH were also abnormally elevated in more than 80% of patients [23]. In severe cases, acute renal failure occurs, leading to elevated BUN indexes [23]. In this study, it was found that the indexes of CK, ALT, AST, LDH, and BUN in mice treated with 3.5 mg•kg −1 and 7 mg•kg −1 of maduramicin were significantly increased in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 50%
“…In general, serum CK of patients shows a sharp increase, which is more than five times higher than the normal level [44]. ALT, AST, Mb, and LDH were also abnormally elevated in more than 80% of patients [23]. In severe cases, acute renal failure occurs, leading to elevated BUN indexes [23].…”
Section: Discussionmentioning
confidence: 92%
“…Jej przebieg może być łagodny (subkliniczny), z bezobjawowym wzrostem stężenia CK, lub może powodować zagrażające życiu powikłania, takie jak: AKI, martwica dużych grup mięśniowych, zespół rozsianego wykrzepiania wewnątrznaczyniowego (disseminated intravascular coagulation -DIC) [13]. W przypadku choroby Haff spektrum objawów oraz powikłań może być bardzo szerokie, rokowanie jest jednak w zdecydowanej większości dobre [10,14,15]. Opisano mimo to przypadki ciężkiego przebiegu choroby, które wymagały stosowania leczenia nerkozastępczego [5], a nawet doprowadziły do zgonu chorych w przebiegu niewydolności wielonarządowej [7,16].…”
Section: Omówienie I Wnioskiunclassified
“…Opisywany chory podawał w wywiadzie poprzedzającym wystąpienie objawów ciężką fizyczną pracę przy zbyt małej podaży płynów. Niektóre badania sugerują, że spożywanie alkoholu, intensywny wysiłek fizyczny czy spożywanie wątrób raków mogą zwiększać ryzyko rozwoju rabdomiolizy po spożyciu ryb lub skorupiaków [14,19]. Ponadto zwiększona ilość spożywanych ryb/skorupiaków jest wprost proporcjonalna do zwiększonego ryzyka rozwoju rabdomiolizy [19].…”
Section: Omówienie I Wnioskiunclassified